Effects of Site of Blood Collection and Duration of Storage on Coagulation Factor V and Factor IX Levels in Fresh Frozen Plasma - R, Loganathan; Kulkarni, Rajendra G; Kar, Rakhee; Abhishekh, B; Basu, Debdatta (Annals of Pathology and Laboratory Medicine, 2020)
Background: As per Indian drugs and cosmetic act & rules 1945 (DCA), 1% or 4 units/month of all components should meet quality control parameter. Aims and objectives: 1.) To assess the level of clotting factors FV and FIX in FFP. 2.) To identify the association between clotting factors FV and FIX in FFP with its mode of collection and storage. Methods: This is a Cross sectional study design done for a period of 20 months. The comparison of the levels of clotting factors such as V and IX between the blood group were carried out by using independent students’ one-way analysis of variance. All statistical analysis was carried out at 5% level of significance and p-value <0.05 were considered as significant. All statistical analysis was done using software IBM PASW statistics (SPSS) version 19.0. Result: The present study was done at a south Indian tertiary care center from January 2016 to August 2017. Around 28,919 FFPs were assessed during this study period. On comparing factor levels between blood bank and camp site, there were no significant difference. Conclusion: In our study, FV and FIX were maintained as per DGHS criteria.